Pelatihan Public Relation dalam Peningkatan Leadership of Tomorrow Pada Seminar Perhumasan Muda - Rahmat Arfan; Indra Akbar; Fitrian Rizky; Ricky Ariansyah; Muntasir Muntasir; Khairul Azmy; Desy Puspita (LPMP Imperium, 2023)
The accelerated development of communication media requires numerous changes and adjustments in all fields, particularly in communication departments that link internal and external organizations. The main problem with the media today is that so much false information, or hoaxes, must be investigated further to determine its veracity. At least within the scope of the organization they manage, it is a requirement for public relations to be able to suppress any information that develops in society. This training utilizes the lecture method and several case studies presented during the training process. The outcomes of this training are that participants comprehend and can enhance their media communication skills for countering fake news and addressing media developments.